The role of basement membrane laminins in vascular function. (October 2020) - Hallmann, Rupert; Hannocks, Melanie-Jane; Song, Jian; Zhang, Xueli; Di Russo, Jacopo; Luik, Anna-Liisa; Burmeister, Miriam; Gerwien, Hanna; Sorokin, Lydia
Abstract: The extracellular matrix is an integral component of the vasculature, contributing to both developmental processes and structural and functional homeostasis. We describe here the types of extracellular matrices that occur in different blood vessel types, ranging from capillaries to veins, venules and arteries, and focus on the endothelial basement membranes and the laminin family of proteins. We summarize data on the molecular composition of endothelial basement membranes, the structure and in vivo expression patterns of the main endothelial laminin isoforms (laminins 411 and 511) and their, to date, deciphered functions in the vasculature. A significant portion of the review focuses on postcapillary venules and leukocyte extravasation and how the endothelial laminins affect adhesion and migration of different leukocyte types, but also how laminins affect endothelial barrier function by modulating expression and localization of endothelial cell-cell junction molecules, and how these effects differ in CNS versus non-CNS tissues. Comparisons are made to small artery dilation in response to shear flow, which has been shown to be dependent on endothelial laminins and junctional complexes. The data discussed support a central role for basement membrane laminins in different aspects of micro- and macro-vessel endothelial function, but also reveal that many open questions remain, including the contribution of perivascular cells which are either embedded or in direct contact with the endothelial cell basement membrane laminins.